Severe Altered Immune Status After Burn Injury Is Associated With Bacterial Infection and Septic Shock - Moins-Teisserenc, Hélène; Cordeiro, Debora Jorge; Audigier, Vincent; Ressaire, Quentin; Benyamina, Mourad; Lambert, Jérome; Maki, Guitta; Homyrda, Laurence; Toubert, Antoine; Legrand, Matthieu (Frontiers in Immunology, 2021)
Introduction: Burn injury is associated with a high risk of death. Whether a pattern of immune and inflammatory responses after burn is associated with outcome is unknown. The aim of this study was to explore the association between systemic immune and inflammatory responses and outcome in severely-ill burn patients. Materials and methods: Innate immunity, adaptive immunity, activation and stress and inflammation biomarkers were collected at admission and day 2, 7, 14 and 28 in severely-ill adult burn patients. Primary endpoint was mortality at day 90, secondary endpoint was secondary infections. Healthy donors (HD) served as controls. Multiple Factorial Analysis (MFA) was used to identify patterns of immune response. Results: 50 patients were included. Age was 49.2 [44.2-54.2] years, total burn body surface area was 38.0% [32.7-43.3]. Burn injury showed an upregulation of adaptive immunity and activation biomarkers and a down regulation of innate immunity and stress/inflammation biomarkers. High interleukin-10 (IL-10) at admission was associated with risk of death. However, no cluster of immune/inflammatory biomarkers at early timepoints was associated with mortality. HLA-DR molecules on monocytes at admission were associated with bacterial infections and septic shock. Later altered immune/inflammatory responses in patients who died may had been driven by the development of septic shock. Conclusion: Burn injury induced an early and profound upregulation of adaptive immunity and activation biomarkers and a down regulation of innate immunity and stress/inflammation biomarkers. Immune and inflammatory responses were associated with bacterial infection and septic shock. Absence of immune recovery patterns was associated with poor prognosis.